A relação entre o nível de evidenciação socioambiental e os fatores da sustentabilidade de empresas do setor elétrico brasileiro - Silva Neto, Eliezer Rodrigues da (2014)
The Annual Social and Environmental Responsibility Report (RARS) of companies in the Brazilian Electric Sector (SEB) is an important channel of communication between the organizations and stakeholders. The objective of this study was to investigate the relationship between the level of environmental disclosure and economic, environmental and social sustainability factors. The research is classified as quantitative descriptive, in which data collection is presented as documental analysis. The analysis was performed in 108 companies electric utilities that published the RARS in 2012. The first important result was the validation by the Cronbach's alpha test of the indices used to measure the level of Environmental Disclosure of the companies surveyed. Then it was found that companies showed more social indicators that environmental, and some companies still fall within the levels "Regular and Low" social and environmental disclosure, which reinforces the thesis that only through regulation, companies will hold disclosures complete. Regarding the main practices of environmental disclosure, it was found that are aimed to publicize the social and environmental policies pursued by companies, and the negative socio-environmental interactions are poorly evidenced by the companies. Regarding the main research study, a positive and significant relationship between the level of Environmental Disclosure, Social and Environmental Factors and Economic Sustainability was found, and between Level of Social Disclosure and Social Sustainability Factors. And the pressure of stakeholders is positively related and significantly with the level of Environmental Disclosure.